DINAMIKA HUKUM ISLAM DAN AKTUALISASI TEORI-TEORI BERLAKUNYA HUKUM ISLAM DI INDONESIA - Rasyid, Muh. Haras (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2013)
This paper titled dynamics of Islamic law and actualization theories of Islamic law in Indonesia. Main problems is how the dynamic development of Islamic law in Indonesia? in solving the problem briefly used methods, such as the study begins with the collection of data from multiple reference literature then written to the qualitative analysis through several approaches such as historical approach, sociological and juridical. Found that the development of Islamic law is very dynamic and competitive since the entry of Islam in Indonesia. Though Islamic law under challenge but it still can grow and synergize with Islamic laws that exist in Indonesia such as customary law and Western law. Of the dynamics, appeared several theories enactment of Islamic law such as the theory of The Creed of Islam, Reception in Complexu theory, Receptie theory and Exit theory. These theories are recorded in the history of Islamic law in the colonial period and the early days of independence. Attention to the meaning and legal basis of these theories in the development of Islamic law from time to time, these theories still exist, and can be actualized in the middle of coaching and the implementation of Islamic law in Indonesia, because it has a strong philosophical foundation and the real sociological foundation. Just depends on the willingness and ability of the people of Islam.